The role of leadership in collective creativity and innovation: Examining academic research and development environments - Huang, Zijian; Sindakis, Stavros; Aggarwal, Sakshi; Thomas, Ludivine (Frontiers in Psychology, 2022)
Leadership is pragmatically linked to innovation adoption and implementation at a team level, as managers oversee the strategic decisions and policymaking, control resources, and moderate the scanning and searching of the environment. Leadership may have different attitudes toward innovation, being conservative, resisting novelties, encouraging change, stimulating creativity, and innovative solutions. Leaders create and support the structures for creative endeavors in the Research and Development (R&D) environment. Some leadership styles have been linked with creativity and innovation, suggesting that innovation may not be promoted by a single leadership style. Focusing on academic R&D environments, the present study assessed the influence of a leader’s behaviors and motivational support on their subordinates’ innovation and creativity. Simultaneously, the paper highlights the involvement of R&D organizations and groups in developing innovative products, services, technologies, and processes that further positively impact a team. All types of leadership, i.e., transactional leadership, transformational leadership, leader-member exchange theory, and ambidextrous leadership, are discussed. The paper attempts to provide new concepts and examines theoretical and practical implications to better understand how the leadership role is executed in an R&D environment to foster team creativity and innovation.